Extracellular Vesicle Mediated Crosstalk Between the Gametes, Conceptus, and Female Reproductive Tract - Qamar, Ahmad Yar; Mahiddine, Feriel Yasmine; Bang, Seonggyu; Fang, Xun; Shin, Sang Tae; Kim, Min Jung; Cho, Jongki (Frontiers in Veterinary Science, 2020)
Extracellular vesicles (EVs) mediated intracellular communication plays an imperative role in the proper completion of different physiological events. Most of the bio-fluids are enriched with several subpopulations of EVs including exosomes and microvesicles (MVs), with the capacity of transferring different functional molecules (lipids, proteins, and nucleic acids) to target cells. Recipient cells upon receiving the signal molecules undergo different changes that positively affect the structural and functional integrity of the cells. This article was aimed to highlight the role of EVs secreted by gametes, the female reproductive tract, and the growing conceptus in the successful completion of different reproductive events related to gestation. EVs associated with the reproductive system are actively involved in the regulation of different physiological events including gamete maturation, fertilization, and embryo and fetal development. In the reproductive system, EVs mediated intracellular communication is not unidirectional but is rather regulated through crosstalk between the reproductive tract and the growing conceptus. These vesicles are secreted from the ovary, oviductal epithelium, endometrium, developing embryo, and the placenta. The cargo inside these vesicles exerts pleiotropic effects on both maternal and embryonic environments. A better understanding of the EVs-mediated crosstalk will be helpful in the development of useful tools serving both the diagnostic as well as therapeutic needs related to female fertility.